ECONOMIC ANALYSIS OF AGRIBUSINESS PAPAYA HAWAII IN NORTH PONTIANAK (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2013)
West Kalimantan, in addition to prioritize the programs to increase food production, also relying on the kind of horticultural crops as one of the new growth in the agricultural sector. The development of horticultural plants have good prospects of other agricultural commodities. This study aims to analyze the economics of agribusiness Papaya Hawaii. This study uses survey methods. Location is determined by purposive in kecamatan pontianak Utara. Population which is the object of research is the entire Papaya Hawai farmers in the District of North pontianak as many as 118 farmers. Sampling in this study determined by a simple random sample method. The sample in this study were a total of 32 farmers from around the Papaya Hawaii farmers in the district of North Pontianak. Data analysis is the analysis of profit, R/C ratio and Break Even Point (BEP). The results show that the profit received by papaya hawaii farmers is Rp 7216585.2 /year. R/C ratio is 3.82. In the agribusiness Papaya Hawai achieved selling price of Rp 1179 with sales volume of 569.3 kg to achieve the BEP. Key words: Profit, R/C ratio, Break Even Point (BEP), Papaya Hawaii.